A prescription for health inequity: Building public health infrastructure in resource-poor settings - Asad Moten; Daniel F. Schafer; Elizabeth Montgomery (Edinburgh University Global Health Society, 2012)
We live in a fortunate time: we have treatments and other essential tools we need to combat AIDS and other epidemics. Health is a human right. But interventions, either overpriced or merely nonexistent, are usually least available in places they are needed the most. A majority of deaths in these resource-poor settings are avoidable and demonstrate a failure of the health care infrastructure.